2021
DOI: 10.3386/w29256
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Mobility in American History: Accounting for Race and Measurement Error

Abstract: A large body of evidence finds that relative mobility in the US has declined over the past 150 years. However, long-run mobility estimates are usually based on white samples and therefore do not account for the limited opportunities available for non-white families. Moreover, historical data measure the father's status with error, which biases estimates toward greater mobility. Using linked census data from 1850-1940, I show that accounting for race and measurement error can double estimates of intergeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
0
10
0
7
Order By: Relevance
“…The results from error-ridden data revealed no remarkable difference in the coefficient on race relative to the coefficient from the simulated model without measurement error. 40 We concluded that measurement error is unlikely to account for the black-white mobility gap, though the issue is an important one, as pointed out by Ward (2020). 41 Method of Income Assignment.…”
Section: Measurement Errormentioning
confidence: 82%
See 2 more Smart Citations
“…The results from error-ridden data revealed no remarkable difference in the coefficient on race relative to the coefficient from the simulated model without measurement error. 40 We concluded that measurement error is unlikely to account for the black-white mobility gap, though the issue is an important one, as pointed out by Ward (2020). 41 Method of Income Assignment.…”
Section: Measurement Errormentioning
confidence: 82%
“…This is similar in spirit to the often-used occscore variable from IPUMS (Ruggles et al 2015), which is based on occupation-specific earnings in 1950. But the scoring used here has much more flexibility, reflecting recent evidence that more flexible scoring provides more reliable comparisons across groups (Inwood, Minns, and Summerfield 2019;Ward 2020;Saavedra and Twinam 2020). Income assignments that would be based on fewer than 50 underlying census observations are supplanted with scores based on a race-and occupation-specific national average (not region-specific) or, if necessary, based on a race-specific one-digit occupation (rather than the three-digit code).…”
Section: B Assigning Income Scores and Ranksmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the measurement error, I adopt the approach of using different measures of the same variable (in this case parental income) as an instrument for annual parental income. It is standard in the literature to use another measure of the same variable to address measurement error/attenuation bias in the OLS estimates (Aizer et al, 2018;Altonji & Dunn, 1991;Angrist & Krueger, 2001;Mani et al, 2012;Modalsli & Vosters, 2019;Ward, 2021). Therefore, I now use parental income from 1993 as an instrument for parental income from 1997, assuming the measurement error in 1993 is uncorrelated with the measurement error in 1997.…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…e literature has long recognized the issue of measurement error in inferring socioeconomic status from a single observation of an occupation (Solon 1992) and recent work has sought to address this by incorporating additional information on grandfather's status (Lindahl et al 2015;Long and Ferrie 2018), dynastic status (Clark and Cummins 2020), uncles (Adermon et al 2019), or by obtaining additional observations of occupational status for a given individual through multiple census linkages (Ward 2020).…”
Section: Robustnessmentioning
confidence: 99%